Facile and Room Temperature Synthesis of Superparamagnetic Fe3O4/C Core/Shell Nanoparticles for Efficient Removal of Pb(II) From Aqueous Solution. Issue 6 (11th February 2019) - Sayed, M.; Abbas, Mohamed; Abdel Moniem, Shimaa M.; Ali, M. E. M.; Naga, S. M.
Abstract: In this work, superparamagnetic Fe3 O4 /C core/shell nanoparticles (NPs) were synthesized using a room‐temperature and green route combining co‐precipitation method, followed by hydrothermal process. The prepared nanoparticle was utilized as an adsorbent for the removal of Pb +2 ions from a wastewater. The effect of various parameters; such as pH, dose of adsorbent, contact time and concentration of lead ions on the adsorption capacity were examined in details. The adsorption capacity (qm) of Fe3 O4 /C NPs was estimated from the Langmuir isotherm curve and was found to be 244 mgg −1 . Interestingly, the produced Fe3 O4 /C NPs exhibited a rapid removal of toxic lead metal ions from wastewater effluents and the adsorption kinetics is well described by pseudo‐second‐order model. Furthermore, the data of Pb 2+ adsorption is best fit for the Langmuir model. Moreover, the Fe3 O4 /C core/shell NPs were recycled and reused for at least five times without a significant loss of adsorption efficiency. Abstract : A cconvenient and cost‐effective hydrothermal approach is developed for the synthesis of highly efficient superparamagnetic Fe3 O4 /C core/shell NPs as adsorbent materials for the removal of toxic lead metal ions from wastewater